Identificación de los daños ocasionados por la roya (Uromyces appendiculatus) en el cultivo de fréjol (Phaseolus vulgaris L.) en la Comunidad de Pisquer, Cantón Mira, Provincia del Carchi - Yacelga Herrera, Eduardo Javier (2019)
SUMMARY The identification of rust in bean cultivation is of utmost importance throughout the cycle that includes the development of the plant, the knowledge that the farmer has acquired through talks, technical programs, research, practices have helped him to implement an adequate management of this disease and thus avoid significant losses at the end of the harvest. The present investigation was carried out in the community of Pisquer, Cantón Mira, Provincia del Carchi, with the objective of identifying the main damages caused by rust (Phaseolus vulgaris L.) and control strategies. This study is based on the method of collecting secondary information, such as primary information obtained through a semi-structured survey applied to ten farmers engaged in bean cultivation. From the analysis of the obtained results, it was established that the rust is considered as an important disease that affects the production of beans; to the quality in the product and therefore to generate economic losses for the farmer. It was possible to identify that the spread of this disease is due to the climatic conditions of the sector, besides the inadequate rotation of the crop makes it difficult to eradicate the pathogen. In conclusion, it was determined that in the Community of Pisquer it is common to find bean crops attacked with this disease, however, the application of preventive measures allow to control significantly the rust in the crop and avoid losses of the product. Keywords: rust, bean, farmer, survey, control.